Creating boundary objects supports knowledge co-development processes: a case study evaluation from the Colorado Front Range - Brown, Hannah L. C., author; Cheng, Antony S., author; Clark, Nehalem C., author; Slack, Andrew W., author; Wolk, Brett H., author; Oxford University Press, publisher (Colorado State University. Libraries, 2024)
This qualitative case study evaluates manager and researcher perceptions of the impact of a place-based, collaborative knowledge co-development process and examines the outcomes of that co-development for changes to management approaches. The USDA Forest Service (Forest Service) Rocky Mountain Research Station General Technical Report 373 (GTR-373) is a codeveloped science synthesis that functions as a boundary object providing a framework for planning, designing, and implementing management action for restoration of ponderosa and dry mixed-conifer forests. The process of creating and socializing the GTR-373 framework fostered continual knowledge exchange and engagement between researchers and managers across different organizations and levels of decision-making. This built trust in the information, improved justification for management action, developed a common foundation for cross-boundary implementation, and increased communication. The framework has been applied across jurisdictions and has been used as a foundational tool for training staff and designing projects. However, adapting the GTR-373 framework across scales remains challenging. Study Implications: This qualitative case study evaluates a co-development process in which researchers and managers from multi¬ple organizations and agencies collaborated to produce a science-informed restoration framework to support forest management on the Colorado Front Range (GTR-373). The process built trust, improved justification for management action, developed a common foundation for implementation, and increased communication. However, cross-boundary management across spatial scales remains challenging, and managers interpret information through organizational mandates and site-specific context. Sustained collaboration between researchers and land managers can help make science actionable and relevant at the appropriate scale for planning and management across expertise and jurisdictional boundaries.
Keywords: collaborative adaptive management; collaboration; knowledge codevelopment; science application; boundary object; forest management